Tratamiento del asma bronquial y su prevención de los alérgenos causantes en niños menos de 5 años en el Subcentro de salud Lucha Obrera. - García Ramos, Washington José (2019)
Among the treatments presented for asthma which is a more recurrent chronic obstructive pulmonary disease in the child population, Objective: to determine palliative treatments such as oxygen therapies, steroid treatment, bronchodilators and hydration etc. They help maintain a control of this disease that is shown in a severe and sometimes fatal condition, but they can also occur in adults and in advanced ages and that is why this disease constitutes a serious problem worldwide. Methodology: a cross-sectional field and descriptive study was carried out for which 83 individuals whose representatives of children diagnosed with asthma in recent years have had an increase in their incidence were surveyed, although their mortality is generally low in relation to morbidity, but it may be life threatening. Results: 41% of the respondents have a history of bronchial asthma, 75% of the inhabitants are not aware that it is a palliative treatment according to the level of asthma severity. Conclusion: the representatives do not know about the illness of their sons or daughters since they do not take the necessary measures for the prevention of allergens in which we have the permanence of pets within their homes the respective asepsis since these are the main triggers of asthmatic episodes. Ecuador is one of the most vulnerable countries to this disease because it is a country of farmers and ranchers where these are the main risk factors and especially to the province of Los Ríos. Having a health education is a very important aspect because it will allow for the correct control of the sick. This research will help us update knowledge about asthma to strengthen new studies. Why it is a cross-sectional study since it is focused on children of the workers struggle health center.